Concordat between Poland and the Holy See as a proven form of peaceful and consensual determination of mutual relations and the legal situation of Catholics living in the territory of the Republic of Poland - Krajczyński, Jan (Prawo Kanoniczne, 2020)
The author of the work attempts to outline the circumstances of execution of consecutive agreements between Poland and the Holy See, and their content. What is pointed at is the specific type of concordats, their subject and evolution in terms of the method of specifying legal norms crucial for both contractual Parties. At the same time, he proposes a new or additional regulation of some issues, including those relating to the institution of marriage, protection of human life, doctoral schools in church research units and bodies authorized to award the doctoral degree in these units, protection of historic sacred buildings and documents of great historical and artistic value stored in church archives. The aforementioned de lege ferenda conclusions are dictated by social changes and new regulations on certain issues in the European Union and Polish law.